Listen to our world - Martin, Bill 1916-2004; Sampson, Michael R. 1952- (Simon & Schuster Books for Young Readers, 2016)
As they awake in the morning, children are invited to listen to the sounds of their world, where parrots squawk in the rain forest, lions roar on the savanna, and more. Includes facts about the animals included and their habitats